Roosting Habits of Red Junglefowl in Orchard Area - Arshad, Muhammad Irshad; Zakaria, Mohamed (2009)
The roosting habits of Red Junglefowl (Gallus gallus spadiceus) was studied in an in orchard area of University Putra Malaysia, Serdang, Selangor Malaysia, planted with Chiku (Achras sapota), Cempedak (Artocarpus integer), Rambutan (Nephelium lappaceum), Pulasan(Nephelium mutabili), Durian (Durio zibethinus) and Kayu Manis (Cinnamomum iners). Roosting trees were identified when the Red Junglefowls started to crow early in the morning and late evening. The study showed that the Red Junglefowl preferred Cempedak trees. One male was observed to use the same Cempedak tree for 33 days and a Rambutan tree for 9 days. Males and females generally roosted at about the same height from the ground. Roosting height varied between 5 m and 9 m depending upon the tree species. Hens with chicks roosted lower (4 m) than those without chicks. Red Junglefowl left the roosting tree before sunrise and went to roost before sunset. Females went to roost earlier than males and the males departed the roosting tree earlier than females.